Delayed enterocutaneous fistula formation secondary to an inverted non-absorbable suture post midline laparotomy closure. (2020) - Yershov, Danylo; Murphy, Paul; Ferguson, Henry
Highlights: Such a delayed manifestation of enterocutaneous fistula secondary to a midline closure suture has not been previously described. We recommend to investigate such patients with a contrast CT scan to visualise the anatomy and an MRI scan to exclude Crohn's disease. The learning point is that inversion of the suture intra-peritoneally post midline laparotomy closure should be avoided. Abstract: Introduction: Enterocutaneous fistula is a well recognised complication of intra-abdominal surgery. Postoperatively, it may occur due to a small bowel injury or an anastomotic leak and usually presents within days or weeks after surgery. Methods: We present a case report. Information was obtained through a retrospective review of the notes, clinic letters, images and the histology report. Results: We present a case of a patient who developed an enterocutaneous fistula 34 years after panproctocolectomy for ulcerative colitis. Imaging was consistent with an enterocutaneous fistula arising from mid-small bowel. A laparotomy and small bowel resection was performed. The enterocutaneous fistula occurred due to an inverted non-absorbable suture post midline laparotomy closure. Conclusion: Suture-related enterocutaneous fistula can be a rare delayed complication of a midline laparotomy closure when a knot is inverted intra-peritoneally. Consideration should be given to either leaving a knot in the subcutaneous fat tissue or feeding it between the rectus sheath and the suture bites.